Source data for "Detailed multi-lake survey reveal high climate sensitivity of Northern lake CO₂ fluxes" - Anonymous during peer-review (Information not available, contact SND for more information, 2022)
This catalogue post is anonymous during the peer-review process.

After publication of the associated manuscript, the name of the PI, potential contributors, and descriptions of the data (metadata) will be provided.

The dataset was originally published in DiVA and moved to SND in 2024.

Denna katalogpost är anonym under peer-review-processen.

Efter publicering av tillhörande manuskript kommer namn på PI, eventuella medverkande och beskrivningar av data (metadata) att anges.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Source data for "Detailed multi-lake survey reveal high climate sensitivity of Northern lake CO₂ fluxes"
Keywords: climate; klimat; lakes; sjöar; greenhouse gases; växthusgaser; carbon dioxide; koldioxid; chemical compounds; kemiska föreningar; environmental research; miljöforskning; Environmental Sciences; Miljövetenskap